2023
DOI: 10.3390/molecules28073255
|View full text |Cite
|
Sign up to set email alerts
|

Mineral, Nutritional, and Phytochemical Composition and Baking Properties of Teff and Watermelon Seed Flours

Abstract: Demonstrated limitations in the mineral and nutritional composition of refined flours have led to calls for the possibility of enriching them with health-promoting supplements, such as high-value non-cereal seeds. Teff and watermelon seeds have been found suitable for the production of gluten-free flour, but so far, their potential to enrich conventional baking flours has not been comprehensively studied. Hence, the present study aimed at farinographic evaluation of dough based on refined wheat flour with addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The highest increase was seen with a 15% addition (from 0.8 to 2.1). As indicated by research conducted by Jaroszewska et al [30], the addition of WSF to wheat flour resulted in a significant increase in water absorption. Other authors [8] reported that bread crumb moisture also increased with the addition of native and germinated watermelon seeds.…”
Section: Basic Properties Of Low-carbohydrate Bread With Different Am...mentioning
confidence: 88%
“…The highest increase was seen with a 15% addition (from 0.8 to 2.1). As indicated by research conducted by Jaroszewska et al [30], the addition of WSF to wheat flour resulted in a significant increase in water absorption. Other authors [8] reported that bread crumb moisture also increased with the addition of native and germinated watermelon seeds.…”
Section: Basic Properties Of Low-carbohydrate Bread With Different Am...mentioning
confidence: 88%
“…Moreover, simple cereals-based flours have low protein content, thus limiting the availability of essential amino acids like lysine and tryptophan, reflecting nutrient imbalances [ 22 ]. Furthermore, traditional millet, rice, and maize flours, although lower in calories and certain essential nutrients, are natural options that bring local flavors and richness in specific fibers and minerals [ 23 ]. They can complement industrial flours by providing dietary variety and cultural adaptation in infant feeding [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%